Satellite data reveal details of glacial isostatic adjustment in the Amundsen Sea Embayment, West Antarctica - M. O. Willen; M. O. Willen; B. Wouters; T. Broerse; E. Buchta; V. Helm (The Cryosphere)
The instability of the West Antarctic Ice Sheet (WAIS) is a tipping element in the climate system, and it is mainly dictated by changes in the ice flow behaviour of the outflow glaciers in the Amundsen Sea Embayment (ASE). Recent studies postulated that the vertical uplift of bedrock can delay the collapse of glaciers in this region. In West Antarctica, bedrock motion is largely caused by a fast viscoelastic response of the upper mantle to changes in ice loads over the last centuries. This glacial isostatic adjustment (GIA) effect is currently poorly understood, since Earth's rheology and the ice-loading history are both subject to large uncertainties in simulations. Moreover, results from data-driven approaches have not yet resolved GIA at a sufficient spatial resolution. We present a data-driven GIA estimate, based on data from GRACE/GRACE-FO (GRACE and GRACE-FO), CryoSat-2 altimetry, regional climate modelling, and firn modelling, which is the first to agree with independent vertical velocities in West Antarctica derived from global navigation satellite system (GNSS) data. Our data combination yields a maximum GIA bedrock motion rate of 43 ± 7 mm a−1 in the Thwaites Glacier region and agrees within uncertainties in the GNSS-derived rate. The data-driven GIA-related bedrock motion may be used in future simulation runs to quantify a potential delay of the collapse of the West Antarctic Ice Sheet due to the stabilization effects induced by GIA. Furthermore it may be used for testing rheological models with low upper-mantle viscosity in conjunction with centennial loading histories.